Burkholderia PglL enzymes are Serine preferring oligosaccharyltransferases which target conserved proteins across the Burkholderia genus - Andrew J. Hayes (Nature Portfolio, 2021)
Hayes et al provide a glycosylation site focused analysis of the glycoproteome of two widely utilized B. cenocepacia strains, K56-2 and H111. This team demonstrates that within these glycoproteomes Serine is the sole residue targeted for protein glycosylation and that glycoproteins/glycosylation sites are highly conserved across B. cenocepacia isolates.